The Impacts Of Consumer-Generated Advertisements On Purchase Intention - Deneçli, Ceyda (Medimond S R L, Via Maserati 5, 40128 Bologna, 00000, italy, 2012)
Advertising is one of the most important factors that both form and change consumer behaviours. Among the significant goals of advertisement are to introduce the brand to the target market, to establish a positive attitude towards the brand and direct the consumers to purchase the brand. Advertisements are delivered to consumers through various commercial media, which have been widespread with the rapid developments in technology. The current media is interactive rather than being conventional thanks to the development of technology. Furthermore, the new opportunities provided by technology have enabled individuals to participate more actively both in the social environment and in media. This interactive environment created by technology in a sense has democratised the media in digital environments. Therefore, consumers are no more mere consumers; they have become the producers of media content. The advertising, affected by these new tendencies both in technology and media, now provides consumers with the opportunity of forming, designing and arranging media content. The means of media and brands become much more attractive and powerful since the active consumers in media can produce, design or arrange the media content. Consumers who have the role of producing content contribute to the promotion of brands. In this study, an advertisement about a brand in social media, the content of which has been produced by the consumer, has been selected and analyzed. The advertisement was shown to the consumers. Attitudes of consumer towards the brand and the advertisement and consumers' tendency to purchase this certain brand before and after the advertisement were analyzed.
Keywords: advertisement; consumer-generated ads; purchasing; consumer attitude; reklam; tüketici tarafından üretilen reklamlar; satın alma; tüketici tutumu